Cytoskeleton and polyploidy after maturation and fertilization of cryopreserved germinal vesicle—stage mouse oocytes - Eroglu, A. (Springer US, 1998)
PURPOSE: Our purpose was to assess the effect of cryopreservation on cytoskeleton of germinal vesicle (GV) mouse oocytes and determine whether irreversible spindle damage and related digyny associated with cryopreservation of metaphase II (MII) oocytes can be avoided. METHODS: The GV oocytes were cryopreserved using a slowcooling (0.5‡C/min) and slowthawing (8‡C/min) protocol in 1.5 M dimethylsulfoxide supplemented with 0.2 M sucrose and analyzed before and during fertilization by multiplelabel fluorescence and differential interference contrast microscopy techniques. RESULTS: When examined after in vitro maturation, the vast majority (>95%) of cryopreserved and control oocytes displayed normal microfilament and microtubule organization. With respect to barrelshaped spindle and normal chromosome alignment, no significant differences were observed between cryopreservation (78 and 86%, respectively) and control (85 and 95%, respectively) groups. In fertilization experiments, spindle rotation, formation of the second polar body, and pronuclear migration were displayed by similar percentages of cryopreserved (96, 94, and 37%, respectively) and control (98, 97, and 45%, respectively) oocytes, indicating normal functionality of the cytoskeleton during this period. However, pronuclear formation was significantly inhibited by cryopreservation (81%) compared with controls (100%). Regarding digyny and polyspermy, no significant increase was observed after cryopreservation (3 and 10%, respectively) compared with controls (3 and 6%, respectively). CONCLUSIONS: Cryopreservation of mouse oocytes at the GV stage is particularly advantageous to circumvent the spindle damage and increased digyny noted after cryopreservation of MII oocytes.